2017
DOI: 10.1111/are.13476
|View full text |Cite
|
Sign up to set email alerts
|

Triploid hard clamsMercenaria mercenariaproduced by inhibiting polar body I or polar bodyII

Abstract: Two types of triploid hard clams Mercenaria mercenaria were produced by inhibiting polar body I (PB1) or polar body II (PB2) with cytochalasin B. Treatments were applied at 22-23°C, with PB1 inhibition starting at 4-7 min postfertilization and ending when PB2 was first observed in control groups, and with PB2 inhibition starting at 17-23 min postfertilization and ending when 80% of control eggs released PB2. Triploid induction success was evaluated by chromosome counting in 2-4 cell embryos and by flow cytomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…This effect has been mainly attributed to the total or partial sterility in triploid animals, which allows them to redirect the energy involved in reproduction to somatic growth (Ruiz‐Verdugo, Racotta, & Ibarra, ; Wang, Guo, Allen, & Wang, ; Zhang et al., ). Triploidy in bivalves may be induced by inhibiting the production of the first or second polar body (Beaumont & Fairbrother, ; Yang & Guo, ). Alternatively, triploid individuals can also be produced by crossing tetraploid females (4N) with diploid males (2N) (Guo, DeBrosse, & Allen, ).…”
Section: Introductionmentioning
confidence: 99%
“…This effect has been mainly attributed to the total or partial sterility in triploid animals, which allows them to redirect the energy involved in reproduction to somatic growth (Ruiz‐Verdugo, Racotta, & Ibarra, ; Wang, Guo, Allen, & Wang, ; Zhang et al., ). Triploidy in bivalves may be induced by inhibiting the production of the first or second polar body (Beaumont & Fairbrother, ; Yang & Guo, ). Alternatively, triploid individuals can also be produced by crossing tetraploid females (4N) with diploid males (2N) (Guo, DeBrosse, & Allen, ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of polyploidy has become popular in bivalve aquaculture ( Ma et al, 2019 ), either due to gonadal sterility ( Piferrer et al, 2009 ; Dheilly et al, 2014 ; Zhang et al, 2017 ), to the increase in the cell volume and lack of compensation of cell number ( Guo and Allen, 1994 ), or even to the increased heterozygosity that promote larger and faster growth in bivalves ( Guo et al, 2009 ; Yang and Guo, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that inhibiting PB2 resulted in a higher TR than inhibiting PB1 in the Yesso scallop. PB1 inhibition leads to abnormal chromosome segregation during second meiosis, which results in tetraploids and aneuploids along with triploids (X. M. Guo, Cooper, Hershberger, & Chew, ; Yang & Guo, ; Yang, Que, He, & Zhang, ). Although TR should theoretically rise with increased salinity and treatment duration because of developmental asynchrony, it also resulted in decreased hatching and survival ratios in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The triploid larvae were obtained using the optimal aforementioned induction parameters and cultured to the spat stage in 20,000‐L tanks. The larvae were fed with fresh Isochrysis galbana , as well as N. closterium and Platymonas subcordiformis, once the shell length reached 160 μm (Meng et al, ; Yang & Guo, ; Y. H. Zhang et al, ), and the quantity of algae was gradually increased from 2,000 to 80,000 cells/mL daily as the larvae grew (G. F. Zhang & Yan, ). The larval density was maintained at 5–6 larvae/mL at the D‐larval stage (Huo et al, ), and the swimming larvae were cultured at 15 ± 0.5°C with 2/3 water changes daily.…”
Section: Methodsmentioning
confidence: 99%